Business plans kit for dummies - Peterson, Steven D. (John Wiley and Sons., 2016)
If you're looking to establish, expand, or re-energize a business, the best place to start is with a sound business plan—and this new edition of Business Plans Kit For Dummies is here to help you get you started. From getting your hands on start-up money from investors to successfully growing or reimaging your venture, it offers everything you need to craft a well-defined business plan that will set you on a course to get your business moving in the right direction